Estudio de propiedades magnéticas en películas ultra delgadas (2024)
T-MOKE and VSM systems were used to characterize thin films of cobalt oxide (CoO) alloy with thicknesses of 2.5 nm (CoO) and 5 nm (MultiCoO). Measurements were conducted for fields below 1000 Oe in a temperature range from 30K to 450K. Variations in the hysteresis curves with changes in temperature and magnetic field were observed. Magnetic properties, such as coercive field and remanence, indicated a phase transition in the range of 147K to 150K, and a decrease in remanence at very high or low temperatures. Both systems showed similar trends between 150K and 300K, although differences were found at lower temperatures due to VSM limitations. The FC and ZFC measurements of the VSM system indicated minimal changes in magnetization above 200K. The effect of temperature on magnetic properties was significant in the T-MOKE system, so it is necessary to use precise techniques to ensure thermal stability.